Plan to identify strategies for intelligent villages of Kalar district: (a study in development geography) - Sakar Mohammed Hasan; Hawbash Ghafoor Saeed; Fatimah Qader Mustafa (QALAAI ZANIST SCIENTIFIC JOURNAL, 2025)
In modern times, the use of social networking platforms has become widespread in all management affairs and rural areas are among the areas where these platforms can be used appropriately. This work is now actively offered in many European countries. And the results obtained from these experiences are a window of hope for the improvement of life in the rural areas and the repair of the problems that have arisen and prevent the collapse of the village social structure and tackle the phenomenon of rural migration. And enlightening the villages will improve the quality of life of the villagers. This study was an investigation of the current situation and planning for rural education in Kalar, Sulaimani province, Iraq. On this basis, a descriptive method based on comparative analysis was used to search for information and collect information using field methods and questionnaire tools. The statistical population of the study was four townships of Kalar city, three villages from each township were randomly selected and generally using the response collection equation. From a total of 262 households in this area and using survey forms, 151 samples were prepared for data collection. The reliability of the questionnaire was confirmed by checking the validity of the questionnaire and with the help of the obtained statistics. The results of this study showed that the current infrastructure for education in the villages of Kalar is in an irregular situation.